Livestock futures to 2020: How will they shape food, environmental, health, and global security? - McDermott, John J.; Enahoro, Dolapo K.; Herrero, Mario (Oxford University Press, 2013)
This book draws together chapters by leading global experts to explore the complex relationship between food security and sociopolitical stability up to roughly 2025. It offers new insights building on lessons learned since the 2008 and 2011 global food price spikes sparked political unrest that toppled multiple governments and spurred a global land rush unlike any seen since the nineteenth century. The volume opens with three broad background papers that discuss the full sweep of the topic and likely scenarios over the coming decade for the global food economy and climate patterns relevant to food production. These chapters are followed by a group of thematic papers, cutting across major world regions to look at core stressors or responses: the policies, technologies, and key resource inputs of the global food system. The last set of chapters explore the political economy of food security strategies in key developing countries and regions. These chapters explore how emerging market firms and governments might attempt to satisfy growth in domestic food demand in the face of various global stressors, through a range of labor, land, technology, trade, water, and related actions or policies, as well as which sociopolitical instability risks might be associated with those strategies.